Analisis Kinerja Keuangan Perusahaan Ditinjau Dari Economic Value Added Dan Market Value Added - Puspitasari, Ratih (STIE Kesatuan, 2010)
The company that intend to survive longer in business must show good performance. It can be reached if the company has good management. One of management goals is making the companyâs value to be optimal. Maximizing the companyâsvalue is not identical with miximizing profit if profit is defined as accounting profit which can be looked at the companyâs profit and loss report. On the contrary, maximizing the companyâs value is the same with profit economically. Investors want the fund invested will yield wealth increase. Thatâs why the managements must create positive value added either economic value or market value added. The identification of questions studied by the author embraces: (1) How is the companyâs financial performance based on EVA? (2) How is the companyâs financial performance based on MVA? (3) How is the correlation between EVA and MVA? The method used by the author in examining the correlation between EVA and MVA is coefficient correlation. The results of this research are: 1) PT Excelcomindo Pratama shows negative EVA in 2006 and 2007. It has minus Rp420.318.299.700 in 2006 and Rp 222.462.046.200 in 2007. 2) PT Excelcomindo Pratama shows positive MVA in 2006 and 2007 respectively as high as Rp51.007.399.396.000 and Rp42.122.148.150.000. 3) PT Indosat has negative EVA in 2006 and 2007. It has minus Rp3.775.842.427.700 in 2006 and Rp1.562.154.654.000 in 2007. 4) PT Indosat has positive MVA in 2006 and 2007 respectively as high as Rp9.535.992.994.000 and Rp108.009.154.993.000. 5) There is positive correlation between EVA and MVA at Excelmindo Pratama and PT Indosat, that is as high as 0,462. It can be concluded that PT Excelmindo Pratama has not been able to create economic value added yet, but it can create positive market value addedsuccessfully in 2006 and 2007. The same happens at PT Indosat as well. PT Indosat has not been able to create economic value added yet, but it can create positive market value added successfully in 2006 and 2007. The correlation between EVA and MVA at PT Excelmindo Pratama and PT Indosat shows positive state as high as 0,462